A review of zero energy housing regulations for low-income households. (2018) - Han, Jung Hoon; Kim, Sumin; Kim, Jun-Hyung; Lee, Sang-Young
This paper reviews zero energy building programs and regulations in the USA, Europe, Australia and South Korea, and suggest the implication of zero energy housing (ZEH) policy for low-income households to allow for better access, management and modification of homes. Low-income households in Australia are most vulnerable to 'energy poverty' due to ever increasing energy costs such as electricity and gas services. This study identifies three barriers in promoting zero energy housing for low-income households, its affordability, accessibility and occupants' behaviours. It suggests that both provision of financial incentives and assistance for zero energy housing retrofit is required as a regulatory practice in Australia.